Driving SME Success: The Impact of Knowledge Sharing and Effective Knowledge Management - Sutrisno, Sutrisno (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
In today's globalized world and heightened business competition, SMEs play an essential role in economic growth. To thrive, they must leverage their key asset: knowledge. This study explores the impact of knowledge sharing and knowledge management on worker performance within SMEs. Drawing upon the theories of knowledge sharing, knowledge management, and individual performance, this qualitative study analyzes relevant studies to understand these relationships. The study involves the collection and synthesis of prior studies on knowledge sharing and management practices in SMEs, examining their effects on worker performance. The findings demonstrate that knowledge-sharing fosters a collaborative work culture boosts operational efficiency, promotes continuous learning, and stimulates innovation. Knowledge management, on the other hand, ensures effective organization and accessibility of critical information, thereby reducing the risk of knowledge loss. Together, these practices enhance worker performance, adaptability, and business growth, creating a dynamic environment that supports SME resilience in a competitive market.